Legal principles of counteraction to corruption and organized crime and the place of administrative and legal regulation among them (Law and Safety, 2020)
Based on the analysis of the current domestic and international legislation, the author has provided characteristics of the legal principles for combating corruption and organized crime.It has been established that the legal principles for combating corruption and organized crime covers currently a large number of regulatory acts of international and national importance; it has been emphasized that a key place among them belongs to administrative and legal regulation.It has been found out that administrative and legal regulation is a form of legal influence on public relations, which is carried out on the basis of the norms of administrative branch of law. Thus, this legal influence operates in the field of public relations that arise as a result of the activities of public law entities, in particular public authorities. Besides, administrative and legal regulation is, first of all, the system of norms that regulate organizational and administrative issues, aspects of the division of competence of public law entities and their legal relationship.The emphasis has been placed on the fact that if we consider the system of legal principles for combating corruption and organized crime, they mostly consist of the rules of administrative law, since they regulate organizational forms of combating corruption and organized crime as a special activity of public authorities, determine the competence of each of the subject of combating corruption and organized crime, establish structural and system aspects of such activities, establish features of control and supervision over the process of its implementation, etc. It has been established that administrative and legal regulation is dominant in the system of legal principles for conducting activities to combat corruption and organized crime in Ukraine.
Keywords: legal principles; regulatory acts; administrative and legal regulation; counteraction to corruption and organized crime